Examination of the Economic Burden of Frailty in Patients With Adult Spinal Deformity Undergoing Surgical Intervention. Issue 1 (January 2022) - Passias, Peter G.; Ahmad, Waleed; Kummer, Nicholas; Lafage, Renaud; Lafage, Virginie; Kebaish, Khaled; Daniels, Alan; Klineberg, Eric; Soroceanu, Alex; Gum, Jeffrey; Line, Breton; Hart, Robert; et al.
Abstract : BACKGROUND: With increasing interest in cost optimization, costs of adult spinal deformity (ASD) surgery intersections with frailty merit investigation. OBJECTIVE: To investigate costs associated with ASD and frailty. METHODS: Patients with ASD (scoliosis ≥20°, sagittal vertical axis [SVA] ≥5 cm, pelvic tilt ≥ 25°, or thoracic kyphosis ≥ 60°) with baseline and 2-yr radiographic data were included. Patients were severely frail (SF), frail (F), or not frail (NF). Utility data were converted from Oswestry Disability Index to Short-Form Six-Dimension. Quality-adjusted life years (QALYs) used 3% rate for decline to life expectancy. Costs were calculated using PearlDiver. Loss of work costs were based on SRS-22rQ9 and US Bureau of Labor Statistics. Accounting for complications, length of stay, revisions, and death, cost per QALY at 2 yr and life expectancy were calculated. RESULTS: Five hundred ninety-two patients with ASD were included (59.8 ± 14.0 yr, 80% F, body mass index: 27.7 ± 6.0 kg/m 2, Adult Spinal Deformity-Frailty Index: 3.3 ± 1.6, and Charlson Comorbidity Index: 1.8 ± 1.7). The average blood loss was 1569.3 mL, and the operative time was 376.6 min, with 63% undergoing osteotomy and 54% decompression. 69.3% had a posterior-only approach, 30% combined, and 0.7% anterior-only. 4.7% were SF, 22.3% F, and 73.0% NF. At baseline, 104 were unemployed losing 971.38 weekly. After 1 yr, 62 remained unemployed losing 50 508.64 yearly. With propensity score matching for baseline SVA, cost of ASD surgery at 2 yr for F/SF was greater than that for NF (81 347 vs 69 722). Cost per QALY was higher for F/SF at 2 yr than that for NF (436 473 vs 430 437). At life expectancy, cost per QALY differences became comparable (58 965 vs 58 149). CONCLUSION: Despite greater initial cost, F and SF patients show greater improvement. Cost per QALY for NF and F patients becomes similar at life expectancy.